Day and night - Evans, Shira; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2016)
Describes how birds tweet and bees buzz in the daylight before entirely different creatures awaken and prowl after dark.
The changing sky -- Your turn! -- Animals in the day -- Your turn! -- Plants in the day -- Your turn! -- Animals in the night -- Your turn! -- Plants in the night -- Your turn!
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 2-5.
Accelerated Reader
Description based on print version record.
Keywords: Day -- Juvenile literature; Night -- Juvenile literature; Earth (Planet) -- Rotation -- Juvenile literature; Day -- Juvenile literature; Night -- Juvenile literature; Earth (Planet) -- Rotation -- Juvenile literature; JUVENILE NONFICTION / Reader - Beginner; JUVENILE NONFICTION / Technology / Aeronautics, Astronautics & Space Science; Day -- Juvenile literature; Electronic books- OSLIS; Electronic books